2011
DOI: 10.1271/bbb.110467
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Cyclopiazonic Acid Biosynthesis Gene Cluster inAspergillus oryzaeRIB 40

Abstract: The cyclopiazonic acid (CPA) nonproducing strain, Aspergillus oryzae RIB 40, does not biosynthesize cycloacetoacetyl-L-tryptophan (cAATrp) due to a truncation in the responsible PKS-NRPS gene. We found that RIB 40 converted cAATrp to 2-oxocyclopiazonic acid, the final product of CPA biosynthesis in A. oryzae. This indicates that the CPA biosynthesis gene cluster, except for the PKS-NRPS gene, is functional in RIB 40.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Inactivation of these three genes resulted in loss of CPA production. Orthologous genes ( cpaD = dmtA ; cpaA = pks-nrps ; cpaO = moaA ) have been identified in A. oryzae and also shown, by gene disruption, to be required for biosynthesis of CPA ( Shinohara et al, 2011 ). Interestingly, the CPA cluster in both of these fungi also contained a putative transcription factor ( cpaR = ctfR1 ), however, disruption of this gene in both A. flavus and A. oryzae did not affect CPA production.…”
Section: Gene Clusters Producing Secondary Metabolites Associated Witmentioning
confidence: 99%
See 1 more Smart Citation
“…Inactivation of these three genes resulted in loss of CPA production. Orthologous genes ( cpaD = dmtA ; cpaA = pks-nrps ; cpaO = moaA ) have been identified in A. oryzae and also shown, by gene disruption, to be required for biosynthesis of CPA ( Shinohara et al, 2011 ). Interestingly, the CPA cluster in both of these fungi also contained a putative transcription factor ( cpaR = ctfR1 ), however, disruption of this gene in both A. flavus and A. oryzae did not affect CPA production.…”
Section: Gene Clusters Producing Secondary Metabolites Associated Witmentioning
confidence: 99%
“…In the initial step in CPA biosynthesis, the PKS-NRPS catalyzes the condensation of L -tryptophan and two molecules of acetyl-CoA to generate cycloacetoacetyl- L -tryptophan (cAATrp) which is then converted by the DMAT to β-CPA. The FAD-dependent oxidoreductase is then responsible for the cyclization of β-CPA to CPA ( Shinohara et al, 2011 ). Interestingly, A. oryzae RIB40, which does not make CPA, was found to have a truncated version of the PKS-NRPS ( cpaA ) gene.…”
Section: Gene Clusters Producing Secondary Metabolites Associated Witmentioning
confidence: 99%
“…Comparison of the cpa gene cluster of the CPA producer A. oryzae NBRC 4177 with that of the non‐producing strain A. oryzae RIB40 revealed deletion of one half of the cpaS gene through telomeric replacement in RIB40 (Figure 1). 88 However, stable‐isotope‐labeling experiments for RIB40 with the CpaS product cAATrp led to the production of 2‐oxo‐CPA and proved that the remaining genes of the cluster, cpaD and cpaO , were still functional. Further conversion of CPA into the less toxic 2‐oxo‐CPA is catalyzed by the putative P450 enzyme CpaH (Scheme ) 88.…”
Section: Cyclopiazonic Acidmentioning
confidence: 99%
“…88 However, stable‐isotope‐labeling experiments for RIB40 with the CpaS product cAATrp led to the production of 2‐oxo‐CPA and proved that the remaining genes of the cluster, cpaD and cpaO , were still functional. Further conversion of CPA into the less toxic 2‐oxo‐CPA is catalyzed by the putative P450 enzyme CpaH (Scheme ) 88. Surprisingly, this additional enzymatic activity is not present in the cpa clusters of toxic CPA‐producing species like A. flavus (Figure 1).…”
Section: Cyclopiazonic Acidmentioning
confidence: 99%
“…In A. flavus , the CPA biosynthetic pathway consisted of 3 genes (cpaS, cpaD, and cpaO) and was situated next to the AF biosynthesis gene cluster (Chang and others ). In A. oryzae , the ability to form CPA is strain‐dependent (Chang and others ); while the cluster is complete in the NBRC 4177 strain, the RIB40 strain is unable to form the mycotoxin due to a truncation of the PKS–NRPS (Shinohara and others ). Studies performed by Liu and Walsh (, ) demonstrated that cpaS encodes a PKS–NRPS responsible for cAATrp formation, while cpaD encodes a cAATrp‐dimethylallyltransferase, leading to β ‐CPA.…”
Section: Mycotoxin Biosynthetic Pathwaysmentioning
confidence: 99%